المسؤولية الجنائية لجريمة التعذيب تحت التحقيق وفق قانون العقوبات الإتحادي لدولة الامارات العربية المتحدة: Criminal responsibility for the crime of torture under investigation according to the Federal Penal Code of the United Arab Emirates - Alhajjaji, Hajaj Naji Nasr; Md Yusof, Arif Fahmi; Nik Wajis, Nik Rahim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص رغم التقدم الحضاري الإنساني والقانوني الذي تشهده البشرية إلا إن أفعال التعذيب التي ترتكب من قبل الموظفين العموميين تجاه المتهمين بهدف حملهم على الإعتراف بجرائم يشتبه انهم ارتكبوها لا تزال مستمرة ، ويعد هذه خرقاً واضحاً لكل الأعراف والقوانين الدولية والوطنية التي تجرم هذه الأفعال ، حيث يهدف هذه البحث الى بيان الاطار القانوني لجريمة تعذيب المتهم لحملة على الإعتراف وفقاً لقانون العقوبات الإتحادي لدولة الامارات العربية المتحدة ، والتمييز بين هذه الجريمة والجرائم الأخرى ذات الأفعال المماثلة ، من خلال الإجابة على أسئلة الدراسة التالية : ما هو مفهوم جريمة التعذيب؟ وما هي أركانها؟ ووما هي الصور المكونة لهذه الجريمة؟ وكيف يمكن التمييز بين هذه الجريمة والجرائم الأخرى المماثل لها ؟ ، حيث تم إتباع المنهج الوصفي التحليلي في هذه الدراسة ، وفي ناهية هذه الدراسة تم التوصل الى عدة نتائج أهمها : ان التنويم المغناطيسي، وجهاز كشف الكذب، والإستجواب المطول الإستجواب تحت تأثير التخدير (عقار الحقيقة) ، تمثل ضغطاً على حرية المتهم في الدفاع عن نفسه، وأن المشرع في دولة الإمارات قد احال النتيجة في القصد المتعدي والمتمثلة في وفاة المجني عليه إلى جريمة القتل الخطأ، استناداً إلى نص الفقرة الأولى من المادة رقم (387) من قانون العقوبات الاتحادي. Abstract Despite the civilized human and legal progress that humanity is witnessing, the acts of torture committed by public officials against the accused in order to get them to confess to the crimes they are suspected of committing are still continuing, and this is a clear violation of all international and national norms and laws that criminalize these acts, as this research aims To clarify the legal framework for the crime of torturing the accused to drive a confession in accordance with the Federal Penal Code of the United Arab Emirates, and to distinguish between this crime and other crimes with similar acts, by answering the following study questions: What is the concept of the crime of torture? And what are its pillars? And the components of this crime? How can this crime be distinguished from other similar crimes? , where the descriptive analytical method was followed in this study, and at the end of this study several results were reached, the most important of which are: the hypnosis, the lie detector, the prolonged interrogation, the interrogation under the influence of anesthesia (the truth drug), put pressure on the freedom of the accused to defend himself And that the legislator in the UAE has referred the result of the infringing intent represented in the death of the victim to the crime of manslaughter, based on the text of the first paragraph of Article No. 387 of the Federal Penal Code.